Our Lady of Velenkanni Cross in Worli village - Mumbai Archive Project Team (Jio Institute, 2024)
Our Lady of Velenkanni Cross in Worli village was installed in 1875. Next to it is a shrine dedicated to the Blessed Virgin Mary. The cross is associated with the Basilica of Our Lady of Good Health, also known as the Sanctuary of Our Lady of Velankanni, a major Christian pilgrimage centre located in the town of Velankanni, Tamil Nadu.